The Influence of Income Level, Self-Assessment System, and Tax Literacy on MSME Taxpayer Compliance - Monika Verliana Sunarti; Retno Kurnianingsih (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of income level, the self-assessment system, and tax literacy on the tax compliance of MSME (Micro, Small, and Medium Enterprises) taxpayers. This research adopts a quantitative approach with data collected through questionnaires. The data used in this study is primary data. The population of this research consists of MSME taxpayers registered as partners or beneficiaries of the Department of Cooperatives and Small and Medium Enterprises in the Special Region of Yogyakarta. The sample consists of 57 respondents, selected using non-probability sampling with a purposive sampling technique. Data analysis was conducted using multiple linear regression analysis. The tests were carried out using the SPSS application. The results of the study reveal that income level has a significant influence on the tax compliance of MSME taxpayers. However, the self-assessment system and tax literacy do not show any significant influence on MSME taxpayer compliance.